1) 3x + 2y = 8
2) 2x - y = 3
To solve this system of equations, we can use the method of substitution or elimination. Let's use the substitution method:
From equation 2) we can rearrange it to solve for y:
y = 2x - 3
Now we substitute this expression for y into equation 1):
3x + 2(2x - 3) = 8
3x + 4x - 6 = 8
7x - 6 = 8
7x = 14
x = 2
Now, substitute this value of x back into the equation y = 2x - 3:
y = 2(2) - 3
y = 4 - 3
y = 1
Therefore, the solution to this system of equations is (2,1).
e. What two equations from those above would form a system with one solution?
You can list the 2 equations here
AND give the solution (x,y) for both equations, HERE show all work
1 answer